Daya hambat kombinasi madu mangga (Mangifera indica)-susu probiotik terhadap pertumbuhan Eschericia coli ATCC 6538 dan Staphylococcus aureus ATCC 8739 - Andyanita Hanif Hermawati; Aryati Aryati; Isnaeni Yudi Haryanto (Pharmaciana, 2016)
Growth inhibitory activity of combination of mango honey-probiotic milk produced by Lactobacillus acidophilus (L.a) and Lactobacillus casei (L.c) against E. coli and S. aureus has been studied. The fermented milk was prepared by inoculating each probioticin milk at 43ºC and then incubated at room temperature for 24 hours. Diffusion agar technique by using nutrient agar media was used to assess the minimum inhibition concentration (MIC). Result of the research showed that pH of fermentation broth of the probiotic milk reached 5. Biomass obtained that calculated by Total Plate Count of L.a and L.c was 1.3 x 107 cfu/mL and 20.7 x 1013 cfu/mL respectively. Inhibition zone diameter ofthe mangohoney-L.c showed an optimum antimicrobial effect against tested bacteria at 1:9 ratio. The MIC value against E. coli and S. Aureus was 15.7 ± 6,1 mm and 13.3 ± 3.0 mm respectively. The activity of mango honey-L. aexhibite dan optimum antimicrobial effect against tested bacteria at 2:8.The MIC value againstE. coli and S. Aureuswas14,7 ± 1,1mm and 13.3 ± 1.3mm respectively.